Carbon Monoxide Diffusion Through Porous Walls: Evidence Found in Incidents and Experimental Studies - Vermesi, Izabella; Restuccia, Francesco; Walker-Ravena, Carlos; Rein, Guillermo (Frontiers in Built Environment, 2018)
It has been reported recently that carbon monoxide (CO) diffuses through gypsum board at a surprisingly high rate (Hampson, et al., 2013). Because CO is poisonous and a by-product of systems typically present in residential housing like boilers, generators and automobile engines, this finding could have a significant impact on the safety standards published by National Fire Protection Association (NFPA) and International Code Council (ICC). In the US, state legislation mandates the requirements for CO detection and warning equipment to be installed, but currently only enforces CO detection if there are communicating openings between the garage and occupied areas of a building. Therefore, there is a need to find out whether CO indeed diffuses through porous walls. In addition to investigating the validity of the experiments by Hampson (Hampson, et al., 2013), this paper also collects a series of instances in the literature that show the diffusion of CO or other carbon-based gases. We have found a number of actual incidents and laboratory experiments which confirmed the transport of CO through other types of porous walls. We also found studies on the transport of other hydrocarbon gases with larger molecules than CO that can also diffuse through porous walls. We have also analyzed in detail the data from the recent experiments with a mass transfer model and confirm the validity of the findings for gypsum board. After 200 min, the CO concentration in the control chamber was around 200 ppm, which enough to affect people. Our analysis independently confirms that CO can diffuse through porous walls at a fast rate and that the phenomena merits further research for consideration in life safety standards.